IS MULTILINGUAL LIFE PRACTICE OF PUPILS A POTENTIAL FOCUS FOR GEOGRAPHY LESSONS? - Nikolaus REPPLINGER; Alexandra BUDKE (European Journal of Geography)
It is undeniable that societies as well as our geography classrooms become more and more heterogenous. This change requires new perspectives on how to teach and learn geography. Especially in geography education and it’s interculturally connecting curricula multilingualism appears to offer several advantages over strictly monolingually delivered lessons. The aim of the article is to grasp the reality and potential of multilingual teaching and learning in the subject of geography in German secondary schools as an anchor for further studies on that matter. This article does that by presenting the results of a survey on the current status of multilingual education in the German geography curriculum as well as on the multilingual life practices and experiences of pupils with migration history. While German geography lessons are curriculumwise intended to be taught almost entirely in German, our survey revealed that pupils have positive expectations for multilingual education. In addition, the acquisition of language awareness through mediation tasks and codeswitching exercises might support identity-related and geographical education processes. More specifically, multilin-gualism could be used as a bedrock for a reflective approach towards multiperspectivity in geographical education.